Association Between Ultra-Processed Food Consumption and Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) in Adults - Lila Amila; Kurnia Agustina Sitompul; Maretha Primariayu; Dalilah Salsabila Salma; Siti Aria Rahmani Novianto; Marsha Zahrani; Nadia Mardiana Hudan (International Journal of Medicine and Health, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic liver disease globally, but its association with ultra-processed food (UPF) consumption under the new diagnostic framework has not been systematically synthesized. We systematically searched PubMed/MEDLINE, Embase, Cochrane CENTRAL, Scopus, and Web of Science for observational studies examining habitual UPF intake (NOVA classification) and MASLD/NAFLD in general adult populations using validated outcome ascertainment. Quality was appraised via the Newcastle-Ottawa Scale (NOS) and certainty via GRADE. Eight studies comprising >350,000 adults across six countries met the eligibility criteria, with seven rated as good methodological quality. All eight studies reported a positive association between higher UPF consumption and MASLD risk, with prospective adjusted hazard ratios ranging from 1.18 to 1.50 and cross-sectional odds ratios from 1.33 to 2.50. Additionally, decreasing UPF intake significantly lowered intrahepatic fat (7.7% to 2.6%), and an exposure-response gradient was observed across several cohorts. Approximately two-thirds of the association was mediated by adiposity (attenuated after BMI adjustment), while evidence for hepatic fibrosis remained inconsistent. GRADE certainty was rated as Low for the primary association and exposure-response gradient, and Very Low for intrahepatic fat and fibrosis outcomes. In conclusion, higher habitual UPF intake is consistently associated with an increased burden of MASLD in adults, largely mediated by adiposity. Although observational nature limits direct causality, these findings support restricting UPF consumption while awaiting further prospective studies using explicit MASLD criteria.